2020
DOI: 10.1186/s13000-020-00993-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Atyp.C using UF-5000 flow cytometer in patients with a suspected diagnosis of urothelial carcinoma: a single-center study

Abstract: Background This study evaluated the predictive power of Atyp.C (a parameter of UF-5000 flow cytometer) for patients with a suspected diagnosis of urothelial carcinoma. Methods We analyzed 163 urine specimens from 128 patients with suspected urothelial carcinoma using a fully automated fluorescence flow cytometry analyzer (UF-5000) and evaluated its performance on identifying atypical/malignant urothelial cells. From January 1, 2019 to April 4, 2019, all consecutive specimens for urinary cytopathology were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 15 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…When the UF-5000 count of pathological casts, RTECs, YLCs, crystals and atypical cells were ≥1/µL, ≥7/µL, ≥10/µL, ≥10/µL and ≥0.1/ μL [16], respectively, the sample was microscopically reviewed by phase-contrast microscopy. Other rules that trigger manual microscopy of the urine sample include samples with a high total count (≥100.000 particles/µL), a RBC/YLC abnormal scattergram flag generated by the analyser, a high test strip total protein count (>3 g/L), and a sperm count ≥1/µL.…”
Section: Classification Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the UF-5000 count of pathological casts, RTECs, YLCs, crystals and atypical cells were ≥1/µL, ≥7/µL, ≥10/µL, ≥10/µL and ≥0.1/ μL [16], respectively, the sample was microscopically reviewed by phase-contrast microscopy. Other rules that trigger manual microscopy of the urine sample include samples with a high total count (≥100.000 particles/µL), a RBC/YLC abnormal scattergram flag generated by the analyser, a high test strip total protein count (>3 g/L), and a sperm count ≥1/µL.…”
Section: Classification Of the Resultsmentioning
confidence: 99%
“…Previous research has shown that automated urine sediment analysers, when compared to urinary cytopathology, can identify abnormal cells in unstained, uncentrifuged urine specimens [16,35,36]. Depending on the patient group studied, the sensitivity and specificity ranges from 50.0 to 75.0% and 83.3 to 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost effectiveness of the procedure is questioned and criticized for low performance [ 5 ]. Particularly considering urine cytology, using Sysmex UF in aid or even in replace of manual examination may be an option in the future [ 6 ]. Urinalysis testing requires fresh urine samples for chemical and microscopic examinations in which unstained sediment is used in general.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, bladder cancer is the 10th most common cancer, with 573,000 new cases and 213,000 deaths estimated in 2020 ( Sung et al, 2021 ). Urothelial cancer is the most common type of bladder cancer, accounting for 90%–95% of all cases ( Chen et al, 2020 ; Ren et al, 2020 ). Early-stage urothelial cancer is curable, but invasive urothelial cancer with progressive or recurrent disease usually has a poor prognosis ( Lopez-Beltran et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%